2001
DOI: 10.1128/iai.69.12.7625-7634.2001
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interspecies Regulation of Gene Expression byActinobacillus actinomycetemcomitansLuxS

Abstract: The cell density-dependent control of gene expression is employed by many bacteria for regulating a variety of physiological functions, including the generation of bioluminescence, sporulation, formation of biofilms, and the expression of virulence factors. Although periodontal organisms do not appear to secrete acyl-homoserine lactone signals, several species, e.g., Porphyromonas gingivalis, Prevotella intermedia, and Fusobacterium nucleatum, have recently been shown to secrete a signal related to the autoind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
170
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(182 citation statements)
references
References 54 publications
7
170
1
4
Order By: Relevance
“…Kolenbrander demonstrated that dental plaque is a unique ecosystem and these multiple bacterial species form a community 14) . Recent studies have demonstrated that periodontopathic bacteria produced extracellular signals 5,8,9) . Moreover, although the immunological response related to phagocytosis is able to eliminate bacteria on the surface of biofilm, phagocytic cells cannot phagocytose or kill the bacterial cells within the biofilm 14) .…”
Section: Discussionmentioning
confidence: 99%
“…Kolenbrander demonstrated that dental plaque is a unique ecosystem and these multiple bacterial species form a community 14) . Recent studies have demonstrated that periodontopathic bacteria produced extracellular signals 5,8,9) . Moreover, although the immunological response related to phagocytosis is able to eliminate bacteria on the surface of biofilm, phagocytic cells cannot phagocytose or kill the bacterial cells within the biofilm 14) .…”
Section: Discussionmentioning
confidence: 99%
“…Among the genes that are upregulated during interspecific bacterial interactions are often the genes involved in the production of antibiotics, suggesting that antibiosis may be a common defensive or offensive strategy in microbial interactions (Fong et al, 2001;Harrison et al, 2008;Garbeva and de Boer, 2009). In addition, genes that confer resistance against toxins were also found to be upregulated during competitive interactions, suggesting protection against self-intoxication or against toxins produced by other members of the microbial community (Dantas et al, 2008;Martinez 2008Martinez , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…19) Various and intricate links between LuxS or AI-2-QSS and IUS expression have been reported in some bacteria. [20][21][22][23][24][25][26] However, the presence of such links remains undetermined in V. vulnificus. AI-2 production through the enzymatic action of LuxS is the prerequisite step for AI-2 signaling.…”
mentioning
confidence: 99%